Analysis of 6-bar Bricard linkages - Chai, Woon Huei (2013)
Analyze the deployment paths of a foldable and non-foldable 6-bar linkage.Analyze the energies of cyclohexane conformations.Explore future collaboration between mechanical and chemical engineering. [4th Award]